Developing intensive listening skills: a case study of the long-term dictation tasks using rapid speech - Lee, Seung Chun (Malaysian English Language Teaching Association (MELTA), 2010)
This study investigated the effects of dictation of rapid speech on developing listening skills and the impact dictation had on students’ listening/speaking ability. Fifty undergraduate TESL program students participated in the research. They were given the opportunity to practice listening through dictation (listening cloze) for the AP news segments twice a week for a period of twelve weeks. They were also given three dictation tasks each week (two AP news segments and another news article from the Economist or from CNN). Their job was to produce the whole text of each one through intensive listening and meticulous transcription. They were also engaged once in a dictation task based on a BBC documentary. They achieved significant gains in terms of the TOEFL and dictation scores through dictation practice. In addition, three questionnaires completed by the students shed light on how dictation helped them improve listening and speaking skills.